A systematic review of exercise and psychosocial rehabilitation interventions to improve health-related outcomes in patients with bladder cancer undergoing radical cystectomy. (May 2018) - Rammant, Elke; Decaestecker, Karel; Bultijnck , Renée; Sundahl, Nora; Ost, Piet; Pauwels, Nele S; Deforche, Benedicte; Pieters, Ronny; Fonteyne, Valérie
Objective: Summarizing the evidence on the effects of pre- and postoperative exercise and psychosocial rehabilitation interventions on patient-reported outcomes (PROs) and physical fitness in bladder cancer patients undergoing radical cystectomy. Data sources: The Cochrane Central Register of Controlled Trials, MEDLINE, Embase, Web of Science and the Physiotherapy Evidence Database were searched independently by two authors from inception until 10 November 2017. Cited references of the studies and citing references retrieved via Web of Science were also checked. Review methods: Randomized controlled trials (RCTs) and non-randomized studies assessing effects of exercise and psychosocial interventions in bladder cancer patients undergoing radical cystectomy were eligible. Primary outcome measures were PROs and physical fitness. Risk of bias was assessed using the Cochrane Collaboration tool and the Newcastle–Ottawa Scale. Results: Five RCTs (three exercise and two psychosocial studies) and one non-randomized psychosocial study comprising 317 bladder cancer patients were included. Timing of the intervention was preoperative ( n = 2), postoperative ( n = 2) or both pre- and postoperative ( n = 2). Positive effects of exercise were found for physical fitness ( n = 3), some health-related quality-of-life (HRQoL) domains ( n = 2), personal activities in daily living ( n = 1) and muscle strength ( n = 1). Psychosocial interventions showed positive effects on anxiety ( n = 1), fatigue ( n = 1), depression ( n = 1), HRQoL ( n = 1) and posttraumatic growth ( n = 1). Quality assessment showed most shortcomings with sample sizes and strong heterogeneity was observed between studies. Conclusion: The evidence relating to the effects of exercise in bladder cancer is very limited and is even less for psychosocial interventions.